The SPOSIB SB2 Sicilian Cohort: Safety and Effectiveness of Infliximab Biosimilar SB2 in Inflammatory Bowel Diseases, Including Multiple Switches. Issue 2 (21st February 2020) - Macaluso, Fabio Salvatore; Fries, Walter; Viola, Anna; Centritto, Andrea; Cappello, Maria; Giuffrida, Enrica; Privitera, Antonino Carlo; Piccillo, Giovita; Magnano, Antonio; Vinci, Elisa; Vassallo, Roberto; Trovatello, Antonino; et al.
Abstract: Background: No data on the recently introduced infliximab (IFX) biosimilar SB2 in inflammatory bowel disease (IBD) are available. Methods: The Sicilian Prospective Observational Study of Patients With IBD Treated With Infliximab Biosimilar SB2 is a multicenter, observational, prospective study performed among the cohort of the Sicilian Network for Inflammatory Bowel Disease. All consecutive IBD patients starting the IFX biosimilar SB2 from its introduction in Sicily (March 2018) to September 2019 (18 months) were enrolled. Results: Two hundred seventy-six patients (Crohn disease: 49.3%, ulcerative colitis: 50.7%) were included: 127 (46.0%) were naïve to IFX and naïve to anti-tumor necrosis factor medications (anti-TNFs), 65 (23.5%) were naïve to IFX and previously exposed to anti-TNFs, 17 (6.2%) were switched from an IFX originator to SB2, 43 (15.6%) were switched from the biosimilar CT-P13 to SB2, and 24 (8.7%) were multiply switched (from IFX originator to CT-P13 to SB2). The cumulative number of infusions of SB2 was 1798, and the total follow-up time was 182.7 patient-years. Sixty-seven serious adverse events occurred in 57 patients (20.7%; incidence rate: 36.7 per 100 patient-year), and 31 of these events caused the withdrawal of the drug. The effectiveness after 8 weeks of treatment was evaluated in patients naïve to IFX (n = 192): 110 patients (57.3%) had steroid-free remission, while 56 patients had no response (29.2%). At the end of follow-up, 72 patients (26.1%) interrupted the treatment, without significant differences in treatment persistency estimations between the five groups (log-rank P = 0.15). Conclusions: The safety and effectiveness of SB2 seem to be overall similar to those reported for the IFX originator and CT-P13.